The Bible in the Fourth Industrial Revolution: "What"s in it for me?" - Oliver, Willem H. (HTS teologiese studies, 2020)
The society in which we currently live and operate is globally the Fourth Industrial Revolution (4IR) and locally our (unique) environment or community. Although we are still in a lag period between the 3IR and 4IR, the 4IR already has a global disruptive effect, with artificial intelligence being gradually implemented, with fluid contexts, and where nobody agrees on anything. Deep learning, unlearning and relearning must take place on a daily basis. The question could well be asked if there is any place for the Bible and Christianity in this new vibrant global community.All theology is contextual. Although theology deals with what is most absolute in reality, citing Mellert, it is also relative in that there is never a final or last answer to most religious questions. The handbook and norm for our theology and religion is still the Bible – a compendium of books written approximately 2000 years ago with no new information added to it ever since. The challenge of the church is to make that information contextual in this ‘disruptive’ era and to bring the gospel in a new and fresh way to everybody without compromising the basic truths and normativity of the Bible.This article argues that the Bible should still take centre stage in the academic training of our theological students, in our preaching of the gospel on a daily basis, in our engagement with people in need and in the transformation of our societies in general. As the centre of Jesus’ preaching on earth was the (coming of the) kingdom of God, he also acted as the perfect example of how to establish the kingdom of God and the flourishing life on earth.Contribution: This is a more practical article and puts the notion of the significance of the Bible within the environment of the Fourth Industrial Revolution. As this is a disruptive era, it requires from us to also present the word of God in a ‘disruptive’ way. We will have to present the ‘old’ word of God in a brand-new way so as to make sure that the people of this era will grasp it.